Promoting mental wellbeing among youth Australian Rules footballers through a model of continuous improvement - Couston, Nicky; Hoare, Erin; Hall, Kate (Frontiers in Sports and Active Living, 2024)
The developmental period of adolescence is a known transitional life phase with unique risk and protective factors that can affect mental wellbeing outcomes. This, in combination with the pressures and demand of elite sport, make young elite athletes an important population in which positive mental wellbeing can be explored. This study aimed to examine the state of wellbeing, informed by positive psychology and the Positive emotions, Engagement, Relationships, Meaning, Accomplishment (PERMA) model of wellbeing, in a cohort of young athletes aged 16–19 years in the Australian setting as part of a model of continuous improvement. The objectives of these aims were to inform the development of a wellbeing curriculum for implementation in the Australian Rules Football talent pathway and to assess whether wellbeing presents differently in young athletes relative to the general school-attending population of that same age. Participants were 608 young Australian footballers participating in the developmental talent pathway during 2020 and 2021. There were 299 young male footballers, and 309 young women footballers who completed data collection. Wellbeing was assessed using the Engagement, Perseverance, Optimism, Connectedness, Happiness Measure of Adolescent Wellbeing (EPOCH) which corresponds to the PERMA model of wellbeing, and total mean scores were reported. Engagement and connectedness were similar for the young men and women athletes. Young men reported higher perseverance, optimism, happiness, and overall wellbeing relative to young women. Wellbeing among young athletes appears similar to the general population, however perseverance may be higher among young athletes. These findings form an important component of the continuous improvement model adopted in the football program in that the results informed the development of a tailored wellbeing curriculum program that is reflective of the wellbeing needs of the young athletes.